The cross-correlation of lipid spectrum components in hypertensive patients - Mykytenko, Ya. V.; Buriak, V. V.; Буряк, Віктор Валерійович (Запорізький державний медико-фармацевтичний університет, 2023)
Aim: to define the cross-correlation of lipid spectrum components in hypertensive patients.
Keywords: тези доповідей